Beberapa Faktor yang Mempengaruhi Underpricing Saham Pada Perusahaan Yang Melakukan Initial Public Offering (IPO) Di Bursa Efek Indonesia - Ramadana, Sri Winarsih (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2018)
The purpose of this study is to examine the effect; financial leverage, profitability, underwriter reputation, company age and company size against underpricing of company shares that carried out an initial public offering on the Indonesia Stock Exchange from 2007 to 2013. The data used in this study is cross sectional data, namely prospectus data in the form of annual financial reports company, underwriter data, company age and size issued by the Indonesia Stock Exchange for the period 2007-2013. The data analysis method used is multiple linear regression. Data analysis begins with variable descriptive statistics, classic assumption tests, and hypothesis testing. The results of the research partially show that financial leverage has a positive effect on underpricing, while profitability, the reputation of the underwriter, the age of the company and the size of the company negatively affect underpricing. The results of the study indicate that together (simultaneous) financial leverage, profitability, underwriter reputation, company age and company size influence underpricing.